2008
DOI: 10.1002/adfm.200701407
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Arcing Induced Formation and Growth Mechanisms of Core/Shell Metal/Carbon Nanoparticles in Organic Solutions

Abstract: Well‐graphitized core/shell iron/carbon nanoparticles (Fe@CNPs) were formed in toluene solutions containing Fe(CO)5‐C60/70 via an novel microwave arcing process. High temperature γ‐Fe phase was found to be stable at room temperature when encapsulated inside graphene shells. In the absence of C60/70, the structures of graphene shells are poor. Pre‐synthesized Co nanoparticles were used as templates for the growth of graphene shells in toluene‐C60/70 solutions. Via acid etching and removal of the central core Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 61 publications
2
62
1
3
Order By: Relevance
“…Careful analysis of the irradiated Mg turnings themselves (and of somewhat smaller Mg particles formed during the arcing process) by scanning electron microscopy (SEM) in combination with energy-dispersive x-ray spectrometry (EDXS) confirmed our assumption that the Mg turnings, while clearly showing the impact of violent electrostatic discharges, were covered with a layer of the carbonaceous material formed during solvent decomposition (Figures S10 [14] An electron energy loss spectrum (EELS) was recorded from the specimen region shown in Figure 4 a highlighting the typical near-edge fine structures for the C-K edge (p* and s* peaks of graphite) and also for the Mg-and O-K edges ( Figure S13). [15] These findings were confirmed by an electron diffraction investigation ( Figure S14).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Careful analysis of the irradiated Mg turnings themselves (and of somewhat smaller Mg particles formed during the arcing process) by scanning electron microscopy (SEM) in combination with energy-dispersive x-ray spectrometry (EDXS) confirmed our assumption that the Mg turnings, while clearly showing the impact of violent electrostatic discharges, were covered with a layer of the carbonaceous material formed during solvent decomposition (Figures S10 [14] An electron energy loss spectrum (EELS) was recorded from the specimen region shown in Figure 4 a highlighting the typical near-edge fine structures for the C-K edge (p* and s* peaks of graphite) and also for the Mg-and O-K edges ( Figure S13). [15] These findings were confirmed by an electron diffraction investigation ( Figure S14).…”
supporting
confidence: 60%
“…[13,14] Visual inspection of the Mg turnings after microwave irradiation clearly revealed that the morphology of the Mg metal surface had undergone significant changes and that the originally shiny Mg surface was now covered with dark material, presumably resulting from THF decomposition (see below).…”
mentioning
confidence: 99%
“…The core/shell structure also resulted from PLA in liquid toluene with a cobalt target [39]. In addition, the formation of core/shell nanoparticles using metals such as gold, silver, and iron oxide have been reported [40,41]. Even though the carbon shell shown in this paper is unusual, it has many advantages regarding the simple and versatile technique without added chemical reagents.…”
Section: Resultsmentioning
confidence: 83%
“…As a matter of fact, some core/shell nanoparticle systems, such as gold, silver, or iron oxide in graphitic shells prepared by PLAL or other methods in liquid have been reported in literatures. 16,[20][21][22] Almost with no exception, these systems were produced in aromatic liquid like toluene or benzonitrile, 16 while those nanoparticles prepared in hexane, a linear hydrocarbon, by laser ablation did not show any graphitic shell structure. 9,11 It can be deduced that the aromatic ring structure of the liquid is an essential condition to form the graphitic shells.…”
Section: -mentioning
confidence: 99%